Comparing the effects of nursing versus peer-based education methods on the preoperative anxiety in infertile women: An RCT - Farahnaz Farnia; Abbas Aflatoonian; Athareh Kalantari (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Background: Preoperative anxiety is a common event in patients expecting surgery. Education can play an important role in reducing the negative effects of anxiety on the response to treatment. Therefore, identifying the appropriate method is important. Objective: The aim of this study was comparing the effects of nursing versus peer-based education on the preoperative anxiety in infertile women. Materials and Methods: In this randomized clinical trial, 198 eligible infertile women were evaluated in three groups (n = 66/each): the nurse-educated, peer-educated, and the controls. The Spielberger State-Trait Anxiety Inventory was filled out by all participants for measuring the patient anxiety at the time of hospital admission and prior to surgery. Participants in the nurse-educated and peer-educated groups received a group education program by a nurse or peer, respectively, after the initial completion of the Spielberger State-Trait Anxiety Inventory. Results: The mean score anxiety was 44.47, 46.92, and 42.60 at the time of hospital admission and 39.38, 41.06, and 43.42 prior to surgery in nurse-educated, peer-educated, and the control groups, respectively. There was a significant difference in the mean score of anxiety in each group before and after the intervention (p < 0.0001). However, the difference between the groups was not significant. Conclusion: Our findings demonstrate that nursing and peer education programs both reduce the preoperative anxiety. Hence, optimal use of the peer's potential regarding the compensation for staff shortage for preoperative education as well as investigating the effect of individual education is suggested for further studies.